2022
DOI: 10.3389/fonc.2022.925041
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insight on Regulations of FBXW7 and Its Role in Immunotherapy

Abstract: SCFFBXW7 E3 ubiquitin ligase complex is a crucial enzyme of the ubiquitin proteasome system that participates in variant activities of cell process, and its component FBXW7 (F-box and WD repeat domain–containing 7) is responsible for recognizing and binding to substrates. The expression of FBXW7 is controlled by multiple pathways at different levels. FBXW7 facilitates the maturity and function maintenance of immune cells via functioning as a mediator of ubiquitination-dependent degradation of substrate protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 196 publications
0
3
0
Order By: Relevance
“…Regarding gene mutation patterns, recent studies have determined that increased mutation in KRAS and FBXW7 have been implicated as immunosuppressive biomarkers that play a role in poor immunotherapeutic responses in CRC. 43 , 44 Additionally, high co-expression of HAVCR2 and MSLN have been shown to be prevalent in several cancers and may also be vulnerabole to the use of CAR-T therapies. Pre-clinical studies have shown the utility of CAR-T therapy in an MSLN high ovarian cancer model.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gene mutation patterns, recent studies have determined that increased mutation in KRAS and FBXW7 have been implicated as immunosuppressive biomarkers that play a role in poor immunotherapeutic responses in CRC. 43 , 44 Additionally, high co-expression of HAVCR2 and MSLN have been shown to be prevalent in several cancers and may also be vulnerabole to the use of CAR-T therapies. Pre-clinical studies have shown the utility of CAR-T therapy in an MSLN high ovarian cancer model.…”
Section: Discussionmentioning
confidence: 99%
“…With tumor-infiltrating immune cells and cancer-associated fibroblasts (CAFs), the tumor microenvironment (TME) has emerged as a central player in cancer drug resistance, which constantly evolves during cancer progression and significantly affects treatment efficiency (Liu et al, 2022). FBXW7 is involved in immune evasion that occurs in anti-tumor immune responses, as well as in the regulation of the immune microenvironment, and its mutation or downregulation is more likely to lead to immunotherapy resistance (Xing et al, 2022). Mutation or loss of function of FBXW7 significantly reduces the infiltration of dendritic cells and immune cells, such as macrophages and CD8 T cells, in the tumor microenvironment, thereby promoting resistance to anti-PD-1 therapy (Gstalder et al, 2020;Ding et al, 2023).…”
Section: Regulating the Tumor Microenvironment (Tme) And Immunotherapymentioning
confidence: 99%
“…Similar to CRC, preclinical studies and case reports have shown that deletion of FBXW7 is associated with resistance to anti-PD-1 immunotherapy in melanoma patients (Iraz et al, 2017;Gstalder et al, 2020). In addition, FBXW7 is strongly associated with tumor immune cell infiltration and immunotherapeutic responses in renal cell carcinoma(RCC) (Xing et al, 2022). NFAT1 is a member of the nuclear factor of activated T cell (NFAT) family, which is involved in many aspects of cancer, including carcinogenesis, cancer metastasis, formation of the tumor microenvironment, and immunotherapeutic response (Jiang et al, 2019).…”
Section: Other Tumorsmentioning
confidence: 99%
“…A major cause of recurrence, metastasis and drug resistance in breast cancers lacking effective anti-hormonal targets is the formation of immunosuppression in the tumor microenvironment, and clinical breast cancer treatment strategies have shown great interest in single agent co-immunosuppressive therapy [ 110 ]. Crosstalk between FBXW7 and related binding proteins regulates immune cell numbers, metastasis, and the premetastatic niche, playing a role in breast cancer immunosuppression [ 111 , 112 ] (Fig. 5 F).…”
Section: Crosstalk Between Fbxw7 and Binding Proteins In Bc Progressionmentioning
confidence: 99%